2016
DOI: 10.1007/s00436-016-5332-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an indirect rMPSP enzyme-linked immunosorbent assay for the detection of bovine Theileria infection in China

Abstract: Bovine theileriosis, a tick-borne protozoan disease caused by Theileria annulata, Theileria orientalis and Theileria sinensis, is widespread in China and is a serious economic problem for the Chinese livestock industry. In this study, recombinant major piroplasma surface proteins (MPSP) of T. annulata, T. orientalis and T. sinensis based on MPSP genes were expressed in Escherichia coli BL21(DE3). The immunogenicity and specificity of the three purified recombinant MPSP proteins were evaluated with the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…ROC analysis was applied to the rMABbo-iELISA to assess the cutoff value using a batch of samples of known serological status. The cutoff value of 35% obtained in our study is similar to the value obtained by other studies using iELISA based on recombinant antigens and bovine sera [ 16 , 17 ]. Sensitivity and specificity of the rMABbo-iELISA was optimal and very similar to the values reported for the MZ-iELISA [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…ROC analysis was applied to the rMABbo-iELISA to assess the cutoff value using a batch of samples of known serological status. The cutoff value of 35% obtained in our study is similar to the value obtained by other studies using iELISA based on recombinant antigens and bovine sera [ 16 , 17 ]. Sensitivity and specificity of the rMABbo-iELISA was optimal and very similar to the values reported for the MZ-iELISA [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…These parasites are usually found in horses, sheep and cattle. T. sinensis is distributed only in Gansu Province China and is transmitted by Haemaphysalis qinghaiensis (Zhao et al, 2017). In our study, records from dogs infected with B. canis vogeli and T. sinensis provided by veterinarians from clinics indicated that these pet dogs spent most of their time indoors and they had limited exposure to the outside environment with active R. sanguineus and H. qinghaiensis ticks.…”
Section: Resultsmentioning
confidence: 99%
“…It is unsurprising therefore that seroconversion to the MPSP is also strongly correlated with both parasite load and the Ikeda genotype [133]. Another study demonstrated that humoral responses to experimental infection with T. orientalis (via mechanical transfer) are variable and only established after persistent infection [152]. The role of humoral immunity in protecting against T. orientalis infection in adult cattle is unclear.…”
Section: Clinical Disease Infection Dynamics and The Immune Responsementioning
confidence: 99%
“…While a number of serological tests exist for the detection of T. orientalis [29,87,133,152,162], these assays are currently not genotype-specific and in some cases also cross-react with other Theileria species [152,162]. Serological tests are of a similar sensitivity to blood smear examination and are most reliable when the animals are clinically affected, but are unsuitable for testing newly infected animals that have not yet seroconverted [133].…”
Section: Diagnosismentioning
confidence: 99%